Cell surface cathepsin G can be used as an additional marker to distinguish T cell subsets - Adriane Penczek; Timo Burster (Biomedical Reports (Spandidos Publications), 2019)
The serine protease cathepsin G (CatG) is involved in numerous processes associated with the innate and adaptive immune system. During an immune response, neutrophils secrete CatG, which can bind to the cell surface of immune cells to provoke the proteolytic processing of cytokines and chemokines in order to stimulate lymphocytes. The present study analyzed peripheral blood mononuclear cells to characterize T cell populations in terms of their CatG content by flow cytometry. It was identified that CatG was exclusively present on the cell surface of a subset of T regulatory cells (Tregs), cluster of differentiation (CD) 39⁺ Tregs, which expressed CatG in contrast to CD39⁻ Tregs. Additionally, CatG was expressed on double positive CD4⁺CD8⁺ T cells, T helper (Th) 9 cells and Th22 cells, implicating CatG as a novel marker to distinguish certain T cell subsets.
Keywords: cathepsin G; cell surface marker; T cell subsets; CD39⁺ Tregs; Th9; Th22; CD4⁺CD8⁺ T cells